Study Kasus Serta Perawatan Pada Kompressor di PT. Sakura Java Indonesia - Muhammad Ihza Herdianto (Peneliti.net, 2022)
In terms of producing quality products, a quality production process is needed starting from the material to becoming a product, but problems and constraints can arise in the production process or from the tools to support the production process. For this reason, maintenance of production equipment and production support must be carried out frequently to prevent damage that will hinder the production process. FMEA is a structured procedure to identify and prevent as many failure modes as possible. Referring to the results of rounding the average weighted value of severity, occurrence, and detection, data processing is carried out by calculating the Risk Priority Number value in FMEA and from these results to indicate the criticality level of each failure mode. By looking at the results of calculations using the FMEA method, oil filter leaks due to broken rings are resulting in a Risk Priority Number (RPN) of 90, to deal with the problem of oil filter leaks due to broken rings is to carry out preventive maintenance with a period of 5000 hours.